2019
DOI: 10.1249/mss.0000000000002129
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transcranial Direct Current Stimulation on Chronic Ankle Instability

Abstract: Background: Inhibitory control refers to a central cognitive capacity involved in the interruption and correction of actions. Dysfunctions in these cognitive control processes have been identified as major maintaining mechanisms in a range of mental disorders such as ADHD, binge eating disorder, obesity, and addiction. Improving inhibitory control by transcranial direct current stimulation (tDCS) could ameliorate symptoms in a broad range of mental disorders. Objective: The primary aim of this pre-registered m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 77 publications
3
39
0
Order By: Relevance
“…It should be noted that the improvement of 15° inversion in the HD-tDCS group was observed in Week-3 and Week-6, but not in Week-4. This may be due to ongoing adaptation of the participants to the change of SFE training in Week-4 from a bipedal to unipedal stance [ 15 ], a possibility supported by a similar regression observed in the sham group at this timepoint.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…It should be noted that the improvement of 15° inversion in the HD-tDCS group was observed in Week-3 and Week-6, but not in Week-4. This may be due to ongoing adaptation of the participants to the change of SFE training in Week-4 from a bipedal to unipedal stance [ 15 ], a possibility supported by a similar regression observed in the sham group at this timepoint.…”
Section: Discussionmentioning
confidence: 89%
“…Sample size estimation for this study was based upon the results from two previous studies [ 15 , 19 ]. One study demonstrated that 24 sessions of SFE improved joint position sense in people with CAI as compared to proprioceptive sensory exercise; that is, those who received SFE had 20 ± 14% greater improvement [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies implemented a double-blinded design (Vines et al, 2008;Reis et al, 2009Reis et al, , 2013Williams et al, 2010;Kang and Paik, 2011;Thirugnanasambandam et al, 2011;Goodwill et al, 2013;Hendy and Kidgell, 2013;Kim and Ko, 2013;Fujimoto et al, 2014;Steiner et al, 2016;Rumpf et al, 2017;Baltar et al, 2018;Yosephi et al, 2018;Jafarzadeh et al, 2019), in which both the study personnel and participants were not aware of the types of intervention. Five studies used a single-blinded design (Stagg et al, 2011;Naros et al, 2016;Zandvliet et al, 2018;Bruce et al, 2020;Tseng et al, 2020), and the blinding was not reported in other four studies (Karok and Witney, 2013;Looi et al, 2016;Washabaugh et al, 2016;Chen et al, 2020).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%